2015
DOI: 10.1589/jpts.27.523
|View full text |Cite
|
Sign up to set email alerts
|

The effects of extracorporeal shock wave therapy on stroke patients with plantar fasciitis

Abstract: [Purpose] The purpose of this research was to analyze the efficacy of extracorporeal shock wave therapy for the treatment of stroke patients with plantar fasciitis. [Subjects and Methods] This study included 10 stroke patients diagnosed with plantar fasciitis who were administered 3 sessions of extracorporeal shock wave therapy per week. After the last session, they performed stretching exercises for their Achilles tendon and plantar fascia for 30 min/day, 5 times a week for 6 months. The following parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
(35 reference statements)
1
10
0
Order By: Relevance
“…Paralleling this finding, physical function increased after ESWT in the PF patients but still was not comparable to the functional assessments in the control group. Our findings were consistent with earlier reports showing that bodily pain decreased after ESWT (25,26,31,32), which might be related to restoration of a more normal gait pattern (3,21).…”
Section: Discussionsupporting
confidence: 93%
“…Paralleling this finding, physical function increased after ESWT in the PF patients but still was not comparable to the functional assessments in the control group. Our findings were consistent with earlier reports showing that bodily pain decreased after ESWT (25,26,31,32), which might be related to restoration of a more normal gait pattern (3,21).…”
Section: Discussionsupporting
confidence: 93%
“…Positive effects in clinical assessments were observed in the follow-up analysis at 1 and 5 weeks after active rESW finalisation. Also, Kim et al [ 23 ], in a prospective and open-label clinical study of poststroke subjects, evaluated the efficiency of pneumatic rESW in lower limb spasticity associated with plantar fasciitis where the authors observed positive results in all measured parameters, which were much greater at the t 2 measurement time point, suggesting some long-term effect of rESW. These findings are very similar to our results; however, we are not able to refer to follow-up changes.…”
Section: Discussionmentioning
confidence: 99%
“…However, current treatment of spasticity in post-stroke survivors are often unsatisfactory 6 ) . In recent years, studies have reported that ESWT is a safe, noninvasive, alternative treatment for spasticity that does not cause muscle weakness or unpleasant effects in patients with multiple disease of central nerve system 7 , 8 ) .…”
Section: Introductionmentioning
confidence: 99%